2021
DOI: 10.1016/j.hrthm.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the origin of Purkinje ectopy-initiated idiopathic ventricular fibrillation

Abstract: BACKGROUND Purkinje ectopics (PurkEs) are major triggers of idiopathic ventricular fibrillation (VF). Identifying clinical factors associated with specific PurkE characteristics could yield insights into the mechanisms of Purkinje-mediated arrhythmogenicity. OBJECTIVE The purpose of this study was to examine the associations of clinical, environmental, and genetic factors with PurkE origin in patients with PurkE-initiated idiopathic VF.METHODS Consecutive patients with PurkE-initiated idiopathic VF from 4 arrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…To further corroborate our findings with studies including patients with PVCs, we screened the references for eligible papers in two reviews 6,14 . We identified 19 examples of published figures 8,15–28 in which PVCs fall after the end of the T wave in patients with IVF.…”
Section: Discussionmentioning
confidence: 74%
“…To further corroborate our findings with studies including patients with PVCs, we screened the references for eligible papers in two reviews 6,14 . We identified 19 examples of published figures 8,15–28 in which PVCs fall after the end of the T wave in patients with IVF.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, the ventricular wall structure contains sheets of cells that also could have a reduced dimensionality. The Purkinje fiber system and trabeculae have been identified as a source for arrhythmia [ 71 , 72 , 73 , 74 , 75 ]. These arrhythmias can arise as a result of ion channel dysfunction, for example through mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study involving 83 consecutive patients with Purkinje-initiated IVF from 4 arrhythmia referral centers, Surget and coworkers (9) found that Purkinje extrasystoles triggering idiopathic VF originate predominantly from the right ventricle in men and from the left ventricle or both ventricles in women. Although not specifically indicated, that study mainly included patients with SCIVF.…”
Section: )mentioning
confidence: 99%
“…In the present study mainly dealing with LCPVC (n=12), 7 (64%) of the 11 patients with Purkinje ectopy triggering NSPVT were females and in all these 7 patients the left Purkinje system was involved. Triggered activities-as early afterdepolarization or delayed afterdepolarization-are the main mechanisms of Purkinje ectopy and well known to be increased by estradiol (9). This may explain some increase in female prevalence.…”
Section: )mentioning
confidence: 99%